ANALISIS FAKTOR-FAKTOR PENYEBAB CACAT PENGELASAN PIPA API 5L Gr.B PADA PROYEK KONSTRUKSI PIPA - HARI MOEKTIWIBOWO; GALUH SURYA WIJAYANTO; BASUKI ARIANTO (JURNAL TEKNIK INDUSTRI, 2021)
This study aim to analyze the factors that occur any defects of weld and determine patterns and types of weld defects were found in the results of welding joint. in the construction of the pipeline API 5L Grade B along 70 Km from Gresik - Surabaya by PT. XYZ. In this study, the method that use is Seven Tools which is one of the tools in the processing of data for quality improvement, to be good communication on team work, and to decision making, and the results will be applied by the company, And the results of this observation the cause of welding defect is 4M1E, that is Man, Machine, Method, Material and Environment. And the welder does not carry out welding in accordance with WPS (Welding Procedure Specification).Keyword : Quality Control System